2021
DOI: 10.25112/bcij.v1i1.2671
|View full text |Cite
|
Sign up to set email alerts
|

Developing Craft as a Creative Industry Through Tourism

Abstract: This paper examines the position of crafts within the creative industries and considers how this has been affected by the growing links between the creative industries and tourism. A review of the creative industries concept indicates that crafts occupy an ambiguous position between art and tradition, which problematises their relationship with the creative industries. This is gradually changing at the creative and tourism sectors become more closely linked, and craft has become an important element of the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The mentions of replicating the knowledge acquired were in line with the creative tourism literature [14,25,38,80]…”
Section: Replication Of Knowledgementioning
confidence: 68%
See 1 more Smart Citation
“…The mentions of replicating the knowledge acquired were in line with the creative tourism literature [14,25,38,80]…”
Section: Replication Of Knowledgementioning
confidence: 68%
“…Departing from the traditional concept of habitus, capital and field [32][33][34][35][36], the authors present in this paper an up-to-date version of the main thinking tools of Bourdieu (Table 1), incorporating the theoretical underpinnings of creative tourism [14,31]. With the broad concept of culture, both tangible and intangible cultural assets are important in creative tourism [37], where non-sanctioned forms of cultural capital (e.g., internet, media) and informal education [38] coexist alongside family and school (dear to Bourdieu), acting as structuring structures and enabling the reflexive and flexible habitus endowed with intercultural capital [39] to cross over to new fields without the effect of hysteresis [40,41], thus rendering social success, skill development and their applications in the creative tourism subfield [31].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere in China, and in other parts of the world, support for traditional crafts has been used successfully in efforts to grow heritage tourism, which positively impacts local economic vitality. Conversely, tourism has been found to support creativity and vitality in local craft traditions [42]. The focus of the two blacksmithing workshops discussed here on utilitarian crafts and repairing villager's tools makes their products unlikely to appeal to tourists seeking craft objects to purchase.…”
Section: Discussionmentioning
confidence: 95%
“…The focus of the two blacksmithing workshops discussed here on utilitarian crafts and repairing villager's tools makes their products unlikely to appeal to tourists seeking craft objects to purchase. However, research has shown that support for local crafts clearly creates cultural resilience and sustainability, and that larger audiences, including tourists, appreciate observing or participating in craft skills because it helps them to feel more engaged with other places and people and more connected with the environment [42,43]. In the case of the Tibetan village blacksmiths discussed herein, the ways in which they use their knowledge and skills to design individualized tools as needed for specific tasks and to repair damaged existing tools so they can continue to be used for long periods of time is quite different from modern practices of purchasing massproduced items and discarding damaged ones to buy another inexpensive replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional crafts, independently or correlated with cultural and creative tourism, are considered increasingly more a source of economic development (Richards et al, 1998;Horjan, 2011;Dragicevic Curkovic, 2021;Richards, 2021). Crafts tourism tends to be increasingly more appealing, determining positive experiences for tourists and bringing added value to local communities (Baruah, & Sarma, 2016).…”
Section: Why Are Traditional Crafts Relevant For Present-day Society?mentioning
confidence: 99%